2017
DOI: 10.1186/s13045-017-0539-3
|View full text |Cite
|
Sign up to set email alerts
|

AC-93253 iodide, a novel Src inhibitor, suppresses NSCLC progression by modulating multiple Src-related signaling pathways

Abstract: BackgroundThe tyrosine kinase Src is involved in the progression of many cancers. Moreover, inhibiting Src activity has been shown to obstruct several signaling pathways regulated by the EGFR. Thus, Src is a valuable target molecule in drug development. The purpose of this study was to identify compounds that directly or indirectly modulate Src to suppress lung cancer cell growth and motility and to investigate the molecular mechanisms underlying the effects of these compounds.MethodsHuman non-small cell lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The primary antibodies were anti-CXCL8-antibody (60141-2-lg, ProteinTech, 1:1000), anti-DACH1-antibody (10914-1-AP, ProteinTech, 1:1000), and anti-β-actin-antibody ( 60008-1-lg , ProteinTech, 1:2000). Secondary staining and detection were conducted in accordance with standard protocols as previously described [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary antibodies were anti-CXCL8-antibody (60141-2-lg, ProteinTech, 1:1000), anti-DACH1-antibody (10914-1-AP, ProteinTech, 1:1000), and anti-β-actin-antibody ( 60008-1-lg , ProteinTech, 1:2000). Secondary staining and detection were conducted in accordance with standard protocols as previously described [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…EGFR inhibitors, like gefitinib and erlotinib, were found in non-small cell lung cancer (NSCLC) to reduce activation of Src and its substrates, suggesting the prominent role of Src in NSCLC progression. Indeed, some authors showed how, in combination with established therapeutic agents, AC-93253 iodide, a Src-EGFR crosstalk inhibitor, blocked cancer cell growth and motility [73]. In EGFR mutated NSCLC, EMT has been associated with acquired resistance to the EGFR inhibitor erlotinib.…”
Section: Lung Cancermentioning
confidence: 99%
“…Using in vitro melanoma cell line-based screening, we previously identified an inhibitor of SIRT2, AC-93253, as a compound that downregulates the expression of genes involved in melanoma progression and chemoresistance acquisition [49]. This compound was subsequently also identified as an SRC inhibitor [51]. These findings prompted us to perform a more detailed analysis of the role of SIRT2 in melanoma cells.…”
Section: Introductionmentioning
confidence: 99%